The Cost of the Outdoor Cat and Dog: Wildlife Rehabilitation in South Central Pennsylvania - Garrigan, Emily; Young, Tracie; Hagerty, Bridgette (Wildlife Rehabilitation Bulletin, 2021)
Invasive species pose a threat to native wildlife species worldwide. Through predation, competition, disturbance, hybridization, and disease transmission, invasive mammals interrupt natural ecosystem functions. Domestic dogs and cats affect wild populations of mammal, avian, and reptile species. Wildlife rehabilitation centers accept wild animals as patients for treatment after they have had contact with a domestic animal with the goal of releasing them back into the environment. The authors’ objective was to evaluate the impacts of domestic cats and dogs on small mammals and birds located in south central Pennsylvania. Wildlife rehabilitators rely on the public to bring them injured animals. Species bias exists among rescuers, as such, this study was not a comprehensive assessment of the problem in Pennsylvania. Survival of patients admitted to Raven Ridge Wildlife Center in Lancaster County, PA between July 2015 and June 2016 was analyzed based on species, reason for admission, location, and season. Survival of patients who had been attacked by cats was significantly lower than those admitted for any other reason. Cats and dogs impacted 23 species, including three rabies vector species. Eastern cottontails accounted for a majority of cat and dog attacks. Moreover, no admitted avian species survived a dog or cat attack on any occasion. Attacks by both dogs and cats increased during breeding season (March–August) for many species, with most attacks occurring in urban areas. Care for wildlife injured by dogs and cats cost Raven Ridge Wildlife Center an estimated 7,557.00 in one year. Wildlife rehabilitators should focus on reducing the likelihood of these attacks through public outreach. Both cat and dog attacks occurred near locations identified as important breeding habitat for threatened or endangered birds, making prevention of these events a priority.